Pendampingan Peningkatan Santri Unggul Melalui Integrasi Kegiatan Usaha bagi Santri Pondok Pesantren Tahfizh Qur’an Yatim Nurani Insani Yogyakarta - Sari, Utami Tunjung; Bahri, Bahri; Sari, Niken Permata; Artha, Bhenu; Hadi, Antonius Satria; Asri, Cahya Purnama (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The purpose of this community service activity is to provide insight into how to start a business independently. This activity uses a counseling method to increase the understanding and awareness of participants, as well as examples of how to start a business independently. The provision of counseling materials is carried out for one day during working hours. Participants in the community service at the Tahfizh Qur'an Yatim Nurani Insani Yogyakarta Islamic Boarding School were attended by 58 participants. The pre-test showed that the audience who knew about how to start a business was 17.24% and those who did not know about technology adaptation were 82.76%. The results of the post-test showed that the audience who knew about how to start a business was 89.66% and those who knew about technology adaptation were 93.1%. After participating in the community service activity, all participants are expected to have knowledge about how to start a business independently in order to open up employment opportunities.